Implementasi Sistem Informasi Penjualan dan Manajemen Inventory Berbasis ERP Odoo Menggunakan Metode Rapid Application Development pada Pet Shop - Ahmed Amin Ahmed Al Humadi; Anik Hanifatul Azizah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2026)
This study aims to implement a sales and inventory management information system based on Odoo ERP using the Rapid Application Development (RAD) method at Anda Pet Shop, a micro, small, and medium enterprise (MSME) in the pet supplies sector. The RAD method was selected for its ability to accelerate system development through an iterative approach that involves users from the early stages through to testing. The implementation of Odoo ERP has been proven to improve data recording accuracy, speed up transaction processes, and simplify real-time inventory management. Based on system testing conducted using the User Acceptance Test (UAT) method and the Technology Acceptance Model (TAM) approach, it was found that the system was well received by users. The average index scores for Perceived Usefulness (PU) and Perceived Ease of Use (PEU) were 87.78% and 81.11%, respectively, indicating that the system provides tangible benefits in improving performance and is relatively easy for users to operate. This research offers a practical solution for MSMEs in managing sales and inventory and serves as a reference for the implementation of similar ERP systems in other small-scale businesses.